Produksi Enzim Selulase Dari Bacillus Substillis Dengan Substrat Tandan Kosong Sawit Dengan Metode Perlakuan Awal Asam - Nazaris, Nazsha Nayyazsha; Amraini, Said Zul; Andrio, David (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The cellulase enzyme is a collection of several enzyme that work together to hydrolyze cellulase. Cellulase enzyme are widely used in the textile, food, detergent, bioefuel and pulp and paper industries so that the enzyme needs continue to increase every year. The production of cellulase enzyme using natural substrate which is widely available in Indonesia, namely empty palm bunches as a carbon source as an expensive carboxymethyl cellulase (CMC) substitute and using Bacillus substillis isolates. This study aims to obtain optimum conditions for cellulase enzyme production with acid pretreatment on oil palm empty fruit bunch substrate and variations in pH of the medium using Bacillus substillis. Pretreatment was carried out so that lignocellulose biomass is more easily hydrolyzed and increases glucose level which will enter the next production phase. Variations in the pretreatment were carried out by adding with acids as well as variations in pH 6,5;7,0; and 7,5. Enzyme activity was calculated using the Nelson-Somogyi method. The result showed that the highest enzyme activity was obtained at pH 7,0 and 40ºC at the pretreatment TKS with acid of 0,041 U/ml. Keywords : Cellulase enzyme, Bacillus substillis, pretreatment, oil palm empty fruit bunch